Cold-resistant high-entropy solid electrolyte, solid electrolyte membrane, lithium metal negative electrode, all-solid-state lithium battery and preparation method
Patent Information
- Application Number
- CN202411828327.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-25
AI Technical Summary
Existing lithium batteries show significant reductions in energy density, power capacity and cycle life in low temperature environments, mainly due to the slow diffusion speed of lithium ions in the electrolyte and poor compatibility of electrode interfaces.
A cold-resistant high-entropy solid electrolyte is prepared by composite monomers, initiators and lithium salts. By regulating the polymerization degree of polymer monomers and the types and proportions of initiators, a high-entropy solvation structure and optimized interface chemistry are formed to improve conductivity and interface stability.
The stable operation of lithium batteries in low temperature environments is achieved, the cycle stability and safety of the batteries are enhanced, and excellent electrochemical performance is also shown at room temperature.
Smart Images

Figure CN119890427A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite material preparation, and specifically relates to a cold-resistant high-entropy solid electrolyte, a solid electrolyte membrane, a lithium metal negative electrode, an all-solid-state lithium battery and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles, people have put forward higher and higher demands for the mileage of new energy vehicles, prompting people to develop power-sized batteries with higher energy density. Lithium metal is expected to replace graphite negative electrodes for the next generation of high energy density lithium batteries due to its advantages such as high specific capacity, low density and low electrochemical potential. However, during the operation of the battery, when lithium dendrites grow to a certain size, they are very likely to pierce the diaphragm, causing internal short circuits in the battery, causing serious safety hazards. Therefore, a safer electrolyte system is needed to replace the traditional liquid electrolyte (liquid electrolyte, LE). Gel polymer electrolyte (GPE), as an electrolyte system between all-solid and liquid states, is currently the most practical type of electrolyte system. However, polymer electrolyte batteries need to be above room temperature to operate reliably. When the temperature drops below 0°C, its energy density, power capability and cycle life will drop significantly, thus limiting the application of batteries in cold climates. In order to solve the above problems, the researchers started from the key scientific issues of poor battery performance at low temperatures and found that the problem of poor battery performance at low temperatures is mainly attributed to the slow lithium ion (Li + ) diffusion and charge transfer kinetics, as well as the interfacial compatibility between electrolyte and electrode. Therefore, it is crucial to develop a polymer electrolyte that not only improves bulk conductivity but also improves interfacial chemistry.
[0003] There is a common electrostatic interaction between lithium ions and solvents or anions in the electrolyte, and the solvation configuration formed will affect the conductivity and interface composition. One common method is to use a low dielectric constant solvent to prepare a weakly solvated electrolyte containing an appropriate lithium salt concentration to form a solvation sheath structure rich in anions. Although this method can improve the interface, the solvation of lithium ions will lead to a decrease in ionic conductivity, which ultimately makes the performance of lithium metal batteries (LMBs) at low temperatures unsatisfactory. Regarding the balance between solvation structure and ionic conductivity, recent studies have shown that the above problems can be solved by introducing multiple salts or mixed solvents to form high entropy solutions, and by changing the solvation structure and designing the structure of the interface layer.
[0004] However, existing studies believe that the improvement of battery performance in high-entropy electrolytes with coexistence of multiple anions is usually related to macroscopic high entropy, and few people pay attention to the particularity of the selection of these high-entropy anions, the relationship between them, and their role in polymer electrolytes and even interfaces. There is no clear statement on the selection of multiple anions in the electrolyte. At present, some researchers emphasize that self-polymerizing solid electrolytes generally have the problem that the curing rate cannot reach 100%, so there are still monomers in them. Therefore, a comprehensive analysis of the effects of high-entropy anions on the electrolyte body (monomers, polymer chains) and interfaces is crucial for the design of cold-resistant solid electrolytes. However, how to reasonably design the anion combination in the high-entropy solid electrolyte so that the solid electrolyte can be further improved synchronously from the bulk phase and the interface phase is still an important challenge that is easy to overlook. Summary of the invention
[0005] In view of the problems and defects of the above-mentioned prior art, the object of the present invention is to provide a cold-resistant high-entropy solid electrolyte, a solid electrolyte membrane, a lithium metal anode, an all-solid-state lithium battery and a preparation method.
[0006] The first object of the present invention is to provide a cold-resistant high-entropy solid electrolyte prepared by compounding a monomer, an initiator and a lithium salt;
[0007] The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20.
[0008] Preferably, the lithium salt is one or more of lithium nitrate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorooxysulfonyl)imide, lithium bis(fluorophosphate)imide, lithium bis(oxalatoborate)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, and a composite salt of lithium bis(oxalatoborate)imide and lithium fluorosulfonate.
[0009] Preferably, the initiator is a Lewis acid salt, and the liquid metal ion of the initiator is one or more of lithium, silver, copper, magnesium, tin, lithium, and zinc; the anion of the initiator is one or more of trifluoromethanesulfonyl imide, fluorosulfonyl imide, tetrafluoroborate, hexafluorophosphate, tetracyanoborate, hexafluoroarsenate, hexafluoroantimonate, and trifluoromethyl substituted derivatives of tetrafluoroborate.
[0010] Preferably, the monomer is one or more of 1,3-dioxolane, tetrahydrofuran, ethylene oxide, trioxymethylene, and fluoroethylene carbonate.
[0011] A second object of the present invention is to provide a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, comprising the following steps:
[0012] S1, mixing and stirring the monomer, initiator and lithium salt to uniformly disperse them to obtain a liquid precursor solution;
[0013] The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20;
[0014] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 6 to 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0015] Preferably, in step S1, the stirring and dispersing time is 90 to 240 minutes.
[0016] The third object of the present invention is to provide a solid electrolyte membrane, which is made of the above-mentioned cold-resistant high-entropy solid electrolyte.
[0017] Preferably, the thickness of the solid electrolyte membrane does not exceed 45 μm.
[0018] The fourth object of the present invention is to provide a lithium metal negative electrode, which is obtained by compounding a lithium metal sheet and the above-mentioned cold-resistant high-entropy solid electrolyte using an in-situ method.
[0019] The fifth object of the present invention is to provide an all-solid-state lithium battery, comprising a positive electrode, a lithium metal negative electrode, and a solid electrolyte membrane located between the positive electrode and the lithium metal negative electrode, wherein the lithium metal negative electrode is the above-mentioned lithium metal negative electrode, and the solid electrolyte membrane is the above-mentioned solid electrolyte membrane.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The cold-resistant high-entropy solid electrolyte provided by the present invention can not only form a lithium metal negative electrode in situ by contacting with metallic lithium, reduce the lithium deposition overpotential (as low as 17.4 mV), and induce uniform lithium deposition; but also reduce the interface resistance between the electrode and the electrolyte;
[0022] (2) The cold-resistant high-entropy solid electrolyte provided by the present invention achieves a balance between the solvation structure and the ionic conductivity by regulating the degree of polymerization of the polymer monomers, and by rationally designing the interface chemistry, lithium is rapidly deposited and dendrite growth is inhibited, so that the synthesized all-solid-state lithium battery can be applied to low-temperature environments. In addition, the present invention uses the interaction between initiators to control the monomer chain length, which makes the symmetrical battery assembled from the cold-resistant high-entropy solid electrolyte capable of operating at room temperature and high current (10 mA cm -1 ) can be stably cycled for 2000h, and the all-solid-state lithium battery can still obtain 65mAh g after 2700 cycles. -1 When the ambient temperature of the battery drops below -20℃, the symmetrical battery can cycle stably for 600h, and the all-solid-state lithium battery can cycle stably for 600h at -20℃ and 20mAg.-1 After 150 cycles under the same conditions, it can still maintain >110mAh g -1 The high capacity exceeds 93% of the initial capacity and has excellent electrochemical performance; therefore, the cold-resistant high-entropy solid electrolyte provided by the present invention significantly improves battery safety, temperature adaptability, cycle life and stability, and has broad military and civilian application prospects in the field of new energy batteries that pursue high safety;
[0023] (3) The lithium metal negative electrode provided by the present invention forms an all-solid-state lithium battery through spontaneous polymerization, which can be prepared quickly and can be produced on a large scale. In addition, the preparation method adopted is simple and easy, with low operating cost, which is conducive to large-scale commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The scanning electron microscope image and X-ray diffraction image of the lithium metal negative electrode prepared in Example 9 of the present invention;
[0025] in, Figure 1 (a) is a scanning electron microscope image; Figure 1 (b) is an X-ray diffraction pattern, and the inset is a digital image of the lithium metal negative electrode;
[0026] Figure 2 This is an in-situ optical microscope image of the lithium metal negative electrode prepared in Example 9 of the present invention;
[0027] Figure 3 Digital photos of LED lamps in normal test state, flexibility test state, safety test state and cold-resistant test state, assembled into soft-pack batteries using the cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention;
[0028] in, Figure 3 a is the normal test state; Figure 3 b is the flexible test state; Figure 3 c is the safety test status; Figure 3 d is the cold resistance test state;
[0029] Figure 4 A comparison chart of cycle test results of a half-cell, a symmetric cell and a full cell assembled with a cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention and a commercial ether electrolyte;
[0030] in, Figure 4 a is a half-cell; Figure 4 b is a symmetrical battery; Figure 4 c is a full battery, and the FNB in the figure refers to a battery composed of a cold-resistant high-entropy solid electrolyte, while Liquid refers to a battery composed of a commercial ether electrolyte;
[0031] Figure 5Gel chromatograms of the cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention, and the solid electrolytes prepared in Comparative Example 1 and Comparative Example 2;
[0032] Among them, Example 1 corresponds to the cold-resistant high-entropy solid electrolyte prepared in Example 1, Example 2 corresponds to the solid electrolyte prepared in Example 1, and Example 3 corresponds to the solid electrolyte prepared in Example 2;
[0033] Figure 6 Scanning electron microscope images of the surface and cross-section of the original and 50-cycle cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention;
[0034] in, Figure 6 a is a scanning electron microscope image of the original surface of the cold-resistant high-entropy solid electrolyte; Figure 6 b is a scanning electron microscope image of the original cross section of the cold-resistant high-entropy solid electrolyte; Figure 6 c is a scanning electron microscope image of the surface after 50 cycles; Figure 6 d is the cross-sectional scanning electron microscope image after 50 cycles;
[0035] Figure 7 These are digital photos of the cold-resistant high-entropy solid electrolytes prepared in Example 1, Example 2 and Example 3 of the present invention after spontaneous polymerization. DETAILED DESCRIPTION
[0036] The following is a description of the embodiments of the present invention. Figures 1 to 7 , the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt;
[0038] The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20.
[0039] Specifically, the lithium salt is one or more of lithium nitrate (LiNO3), lithium bis(fluorosulfonyl) imide (LiFSI), lithium bis(trifluoromethanesulfonyl) imide (LiTFSI), lithium bis(fluorooxysulfonyl) imide (LiDFOB), lithium bis(fluorophosphate) imide (LiDFP), lithium bis(oxalatoborate) imide (LiBOB), lithium trifluoromethanesulfonate (LiOTF), lithium bis(trifluoromethylsulfonyl) imide (LiNTf2), lithium hexafluorophosphate (LiPF6), and a composite salt of lithium bis(oxalatoborate) imide and lithium fluorosulfonate (LiN(SO2C2F5)2).
[0040] Specifically, the initiator is a Lewis acid salt, and the liquid metal ion of the initiator is one or more of silver, copper, magnesium, tin, lithium, and zinc; the anion of the initiator is trifluoromethanesulfonyl imide (TFSI - ), fluorosulfonyl imide (FSI - ), tetrafluoroborate (BF 4- ), hexafluorophosphate (PF 6- ), tetracyanoborate (B(CN)4 - ), hexafluoroarsenate (AsF6 - ), hexafluoroantimonate (SbF6 - ), trifluoromethyl substituted derivatives of tetrafluoroborate (B(CF3)4 - )
[0041] Specifically, the monomer is one or more of 1,3-dioxolane (DOL), tetrahydrofuran (THF), ethylene oxide (PO), trioxymethylene (TOM), and fluoroethylene carbonate (FEC).
[0042] The polymerization degree of the cold-resistant high-entropy solid electrolyte in the present invention can be adjusted. For example, the solid electrolyte obtained from the liquid precursor solution with a large polymerization degree is not conducive to the rapid migration of lithium ions and operation at extreme temperatures; if the polymerization degree is too small, it is not easy to form a safe and reliable solid electrolyte. The polymerization degree of the liquid precursor solution is adjusted by simultaneously introducing different types of initiators.
[0043] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, comprising the following steps:
[0044] S1. Mix the monomer, initiator and lithium salt, and stir and disperse them evenly at room temperature to obtain a liquid precursor solution; the specific dispersion method is selected from one or more of an ultrasonic machine, mechanical stirring, magnetic stirring, planetary stirring, etc.
[0045] The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20;
[0046] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 6 to 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0047] In step S1, the stirring and dispersing time is 90 to 240 minutes.
[0048] The present invention also provides a solid electrolyte membrane, which is made of the above-mentioned cold-resistant high-entropy solid electrolyte, and the thickness of the solid electrolyte membrane does not exceed 45 μm.
[0049] The present invention also provides a lithium metal negative electrode, which is obtained by compounding a lithium metal sheet and the above-mentioned cold-resistant high-entropy solid electrolyte by an in-situ method. Specifically, the lithium metal negative electrode in the present invention is obtained by directly titrating the above-mentioned liquid precursor solution on the surface of the lithium metal sheet, and in-situ generating a lithium metal negative electrode comprising a lithium-philic layer, and the lithium-philic layer is formed instantly when the liquid precursor solution contacts the lithium metal sheet. Therefore, the lithium metal negative electrode in the present invention includes a lithium metal sheet, a lithium-philic layer and a cold-resistant high-entropy solid electrolyte arranged in sequence from bottom to top. The content of the lithium-philic layer in the present invention is controllable, specifically, when the liquid precursor solution is dripped onto the lithium metal sheet, the liquid metal ions in the initiator in the liquid precursor solution will replace lithium to form a metal layer (lithium-philic layer) and a new initiator composed of lithium ions and anions of the initiator, so the content of the lithium-philic layer can be adjusted by adjusting the amount of the initiator in the liquid precursor solution; for example, the increase in active sites is conducive to inducing rapid lithium deposition and interface stability; a small amount of active sites is conducive to providing a larger nucleation space.
[0050] The lithium-philic layer in the present invention is a lithium-philic site interface layer such as a silver layer, a copper layer, a magnesium layer, a tin layer, a lithium layer, a zinc layer, and others.
[0051] The present invention also provides an all-solid-state lithium battery, comprising a positive electrode, a lithium metal negative electrode, and a solid electrolyte membrane located between the positive electrode and the lithium metal negative electrode, wherein the lithium metal negative electrode is the above-mentioned lithium metal negative electrode, and the solid electrolyte membrane is the above-mentioned solid electrolyte membrane. Specifically, the positive electrode, the lithium metal negative electrode and the solid electrolyte membrane are assembled into a battery according to the assembly method of a liquid battery, and then the assembled battery is left to stand for 4-12 hours, and the initiator in the liquid precursor solution spontaneously polymerizes the monomer in the battery, thereby obtaining an all-solid-state lithium battery. The all-solid-state lithium battery synthesized by the present invention can be used not only at room temperature, but also in a low temperature environment.
[0052] The present invention initiates the polymerization of solvent monomers by adjusting the initiator component of the solid electrolyte to form a lithium metal negative electrode that integrates a solid electrolyte, a lithium-philic layer and a lithium metal sheet. The modification of the lithium-philic site can reduce the lithium deposition overpotential (as low as 17mV) and induce lithium deposition. The introduction of a variety of anions can not only induce the polymerization of solvent monomers to ensure the safety of the battery, but also achieve high ionic conductivity, so that the lithium metal negative electrode structure has a more excellent cycle stability. And the preparation method of the present invention based on the above principles can greatly reduce the technical requirements and costs of solid electrolytes, improve controllability and operational feasibility. In addition, the competitive relationship between the various anions can not only reduce the desolvation energy of the solvent from the bulk phase; but also by controlling the chain length of the polymer, a stable lithium-philic site can be formed in situ on the interface, and the cycle stability of the battery at low temperatures can be improved through synergistic effects.
[0053] The technical scheme of the present invention is further described below by specific embodiments. The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0054] The electrochemical performance testing method involved in the embodiment of the present invention is as follows:
[0055] (1) The assembled lithium metal half-cell and symmetric cell were left to stand for 6-12 hours, and then charged at 0.5-10 mA / cm 2 The cycle performance test was carried out at a current density of 0.5-1 mAh / cm 2 The test cycle is 100 cycles, and the coulombic efficiency and stability of the battery are obtained. The charging capacity of each cycle: the discharge capacity = coulombic efficiency.
[0056] (2) The assembled lithium metal full battery was left to stand for 24 hours, and then a cycle performance test was performed at a rate of 1C, with a test voltage of 2.5-3.8V and a test cycle of 150 cycles to obtain the capacity retention rate of the full battery. The discharge specific capacity after 150 cycles was: the first cycle discharge specific capacity = capacity retention rate.
[0057] Embodiment 1
[0058] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is silver tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0059] The mass ratio of monomer, initiator and lithium salt is 163:60:4.
[0060] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0061] S1. Dissolve 0.352 g of lithium bis(fluorosulfonyl)imide, 0.0246 g of silver tetrafluoroborate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, add the mixture into a clean glass bottle with a volume of 10 ml, place a clean magnetic rotor of appropriate size into the bottle and stir for 120 min to obtain a liquid precursor solution;
[0062] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0063] Embodiment 2
[0064] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is silver tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0065] The mass ratio of monomer, initiator and lithium salt is 813:326:20.
[0066] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0067] S1. Dissolve 0.352 g of lithium bis(fluorosulfonyl)imide, 0.0492 g of silver tetrafluoroborate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, stir to obtain a mixed solution, add the mixed solution into a clean glass bottle with a volume of 10 ml, place a clean magnetic rotor of appropriate size into the glass bottle, and stir for 120 min to obtain a liquid precursor solution;
[0068] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0069] Embodiment 3
[0070] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is magnesium hexafluorophosphate and lithium bis(fluorosulfonyl)imide;
[0071] The mass ratio of monomer, initiator and lithium salt is 163:60:4.
[0072] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0073] S1. Dissolve 0.352 g of lithium bis(fluorosulfonyl)imide, 0.0246 g of magnesium hexafluorophosphate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, stir to obtain a mixed solution, add it into a clean glass bottle with a volume of 10 ml, insert a clean magnetic rotor of a suitable size into it and stir for 120 min, observe the fluidity through the glass bottle, as long as it is between the polymer initiation of polymerization and the complete solidification state, a liquid precursor solution is obtained;
[0074] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 6 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0075] Embodiment 4
[0076] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is copper tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0077] The mass ratio of monomer, initiator and lithium salt is 163:60:4.
[0078] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0079] S1. Dissolve 0.352 g of lithium bis(fluorosulfonyl)imide, 0.0246 g of copper tetrafluoroborate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, stir to obtain a mixed solution, add the mixed solution into a clean glass bottle with a volume of 10 ml, place a clean magnetic rotor of appropriate size into the glass bottle, and stir for 240 min to obtain a liquid precursor solution;
[0080] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 10 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0081] Embodiment 5
[0082] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is zinc tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0083] The mass ratio of monomer, initiator and lithium salt is 163:60:4.
[0084] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0085] S1. Dissolve 0.352 g of lithium bis(fluorosulfonyl)imide, 0.0246 g of zinc tetrafluoroborate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, stir to obtain a mixed solution, add the mixed solution into a clean glass bottle with a volume of 10 ml, place a clean magnetic rotor of a suitable size into the glass bottle, and stir for 90 minutes to obtain a liquid precursor solution;
[0086] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0087] Embodiment 6
[0088] The embodiment of the present invention provides a cold-resistant high-entropy solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in the embodiment of the present invention is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is tin tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0089] The mass ratio of monomer, initiator and lithium salt is 163:60:4.
[0090] The present invention also provides a method for preparing the above-mentioned cold-resistant high-entropy solid electrolyte, which specifically comprises the following steps:
[0091] S1. Dissolve 0.375 g of lithium bis(fluorosulfonyl)imide, 0.0246 g of tin tetrafluoroborate and 0.0246 g of lithium nitrate in 1 g of 1,3-dioxolane, stir to obtain a mixed solution, add the mixed solution into a clean glass bottle with a volume of 10 ml, place a clean magnetic rotor of a suitable size into the glass bottle, and stir for 120 min to obtain a liquid precursor solution;
[0092] S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
[0093] Embodiment 7
[0094] The embodiment of the present invention provides a lithium metal negative electrode, and the liquid precursor solution prepared in Example 1 of the present invention is directly titrated on the surface of a lithium metal sheet to generate a lithium metal negative electrode including a lithium-philic layer in situ.
[0095] Comparative Example 1
[0096] This comparative example provides a solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in this comparative example is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is lithium bis(fluorosulfonyl)imide;
[0097] The mass ratio of monomer, initiator and lithium salt is 188:66:5.
[0098] The solid electrolyte is prepared by the following method:
[0099] 0.352 g of lithium bis(fluorosulfonyl)imide (initiator) and 0.0246 g of lithium nitrate were dissolved in 1 g of 1,3-dioxolane; the subsequent preparation method was the same as that in Example 1.
[0100] Comparative Example 2
[0101] This comparative example provides a solid electrolyte, which is prepared by compounding a monomer, an initiator and a lithium salt; the lithium salt in this comparative example is lithium nitrate, the monomer is 1,3-dioxolane, and the initiator is silver tetrafluoroborate and lithium bis(fluorosulfonyl)imide;
[0102] The mass ratio of the monomer, the initiator and the lithium salt is 1000:753:25.
[0103] The solid electrolyte is prepared by the following method:
[0104] 0.704 g of lithium bis(fluorosulfonyl)imide, 0.0492 g of silver tetrafluoroborate and 0.0246 g of lithium nitrate were dissolved in 1 g of 1,3-dioxolane, and the subsequent preparation method was the same as that in Example 1.
[0105] The cold-resistant high-entropy solid electrolytes prepared in Examples 1 to 3 of the present invention and the lithium metal negative electrode structures and electrochemical properties prepared in Example 9 are studied below.
[0106] 1. Characterization of Lithium Metal Anode Structure
[0107] pass Figure 1 It can be seen from a that the surface morphology of the lithium metal negative electrode is flat and smooth, and the lithium-philic sites are coated inside. Figure 1 b It can be seen that the lithium-philic sites are in close contact with metallic lithium, which reduces the interface resistance and effectively improves the interface stability and battery cycle stability.
[0108] pass Figure 2 It can be seen that the lithiophilic sites are formed, the modification of lithiophilic sites at the growth interface induces uniform lithium deposition, and the interface layer gradually thickens with the increase of deposition time, indicating that dendrites can be successfully suppressed.
[0109] 2. Research on the structure and electrochemical performance of cold-resistant high-entropy solid electrolytes
[0110] (1) Battery assembly
[0111] The negative electrode uses a lithium metal sheet (Li, diameter 14mm), the counter electrode uses a metal sheet of 316 stainless steel (SS, diameter 16.2mm) or lithium iron phosphate (LFP) active material as the positive electrode of the full battery, the diaphragm uses a Celgard 2500 battery diaphragm (diameter 19mm), and the electrolyte uses the cold-resistant high-entropy solid electrolyte prepared in Examples 1 to 3, respectively, and a commercial ether electrolyte (40μL LiTFSI (1M) electrolyte added with DOL and DME (1:1v / v) and 1wt.% LiNO3 additives to form a mixed solvent) is used as a comparative electrolyte. The assembly is completed in the order of "negative electrode shell-shrapnel-gasket-negative electrode material-electrolyte-diaphragm-counter electrode-positive electrode shell", and the battery is placed on a button battery manual sealing machine for battery pressure sealing operation, and then electrochemical testing is performed after standing for 12 hours, and assembled into a soft-pack full battery for LED light power supply, flexibility, safety and cold resistance experiments. The above assemblies were all carried out in a glove box protected by argon.
[0112] (2) Test results
[0113] pass Figure 3 It can be seen that the soft-pack battery with a size of 5×5 cm can work well even under conditions of flattening, bending, cutting and extremely low temperature, which shows that the assembled polymer solid-state soft-pack battery based on the cold-resistant high-entropy solid electrolyte of Example 1 of the present invention has excellent flexibility and safety.
[0114] pass Figure 4 It can be seen from a that the half-cell assembled by the cold-resistant high-entropy solid electrolyte of Example 1 of the present invention can still maintain a high coulombic efficiency of 98% after 200 cycles. Figure 4 b It can be seen that the symmetrical battery assembled by the cold-resistant high-entropy solid electrolyte of Example 1 of the present invention always maintains low overpotential fluctuation and shows good cycle stability and can be continuously cycled for more than 620 hours. Figure 4 c It can be seen that the capacity retention rate of the full battery assembled by the cold-resistant high-entropy solid electrolyte of Example 1 of the present invention is 81.1%, which greatly improves the long-cycle stability and energy density of the battery.
[0115] It can be seen that the half-cell assembled with the cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention maintains high coulombic efficiency and long-term stability, and the symmetrical battery always maintains low overpotential fluctuations and exhibits good cycle stability even under fast charging and low temperature. In particular, the performance of the full battery is significantly higher than that of commercial ether electrolytes.
[0116] The present invention studied the polymerization degree of the cold-resistant high entropy solid electrolyte prepared in Example 1, Comparative Example 1, and Comparative Example 2. The results are as follows: Figure 5 As shown, through Figure 5From the results, it can be seen that the molecular weight of the polymer of the solid electrolyte obtained in Comparative Example 1 (corresponding to Example 2) is significantly higher than the molecular weight of the polymer of the cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention, and the excessively high polymerization degree is not conducive to the rapid migration of lithium ions and operation at extreme temperatures, indicating that the solid electrolyte synthesized by a single initiator cannot be used well under low temperature conditions. As the number of salts increases, the molecular weight of the polymer decreases instead, which effectively regulates the chain length and weakens the binding energy between lithium ions and polymers, and therefore plays an important role in weak solvation; and the molecular weight of the polymer of the solid electrolyte obtained in Comparative Example 2 (corresponding to Example 3) is significantly smaller than the molecular weight of the polymer of the cold-resistant high-entropy solid electrolyte prepared in Example 1 of the present invention, and the excessively low polymerization degree is not easy to form a safe and reliable solid electrolyte, indicating that even with the participation of a dual initiator, if the ratio of the initiator to the other components is not within the range specified by the present invention, the synthesized solid electrolyte cannot be used well under low temperature conditions, further indicating that only when a dual initiator is involved and the dual initiator is allocated in a suitable ratio to the other components, a solid electrolyte that can be used well under low temperature conditions can be obtained.
[0117] After 50 cycles of the full battery assembled with the cold-resistant high-entropy solid electrolyte of Example 2 of the present invention, the surface and cross-sectional structures of the cold-resistant high-entropy solid electrolyte were studied and compared with the surface and cross-sectional structures of the original cold-resistant high-entropy solid electrolyte. The results are as follows: Figure 6 As shown, through Figure 6 It can be seen that the lithium-philic sites of the interfacial phase play a role in inducing lithium deposition, so that the lithium metal interface remains flat and free of dendrite formation after multiple cycles, which is conducive to stable lithium deposition and stripping, and provides effective support for high ion migration numbers.
[0118] Figure 7 This is a digital photo of the cold-resistant high-entropy solid electrolyte prepared in Examples 1 to 3 of the present invention after spontaneous polymerization. Figure 7 It can be seen that the morphology of the electrolyte prepared in Example 3 after spontaneous polymerization is closer to liquid than that of Examples 1 and 2, so different initiator types and contents will affect the degree of polymerization.
[0119] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A cold-resistant high-entropy solid electrolyte, characterized in that: It is prepared by compounding monomers, initiators and lithium salts; The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20.
2. The cold-resistant high-entropy solid electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium nitrate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorooxysulfonyl)imide, lithium bis(fluorophosphate)imide, lithium bis(oxalatoborate)imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, and a composite salt of lithium bis(oxalatoborate)imide and lithium fluorosulfonate.
3. The cold-resistant high-entropy solid electrolyte according to claim 1, characterized in that: The initiator is a Lewis acid salt, and the liquid metal ion of the initiator is one or more of silver, copper, magnesium, tin, lithium, and zinc; the anion of the initiator is one or more of trifluoromethanesulfonyl imide, fluorosulfonyl imide, tetrafluoroborate, hexafluorophosphate, tetracyanoborate, hexafluoroarsenate, hexafluoroantimonate, and trifluoromethyl substituted derivatives of tetrafluoroborate.
4. The cold-resistant high-entropy solid electrolyte according to claim 1, characterized in that: The monomer is one or more of 1,3-dioxolane, tetrahydrofuran, ethylene oxide, trioxymethylene, and fluoroethylene carbonate.
5. A method for preparing a cold-resistant high-entropy solid electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing and stirring the monomer, initiator and lithium salt to uniformly disperse them to obtain a liquid precursor solution; The mass ratio of the monomer, the initiator and the lithium salt is 163-813:60-326:4-20; S2. The liquid precursor solution obtained in step S1 is allowed to stand at room temperature for 6 to 12 hours to obtain a cold-resistant high-entropy solid electrolyte.
6. The method for preparing the cold-resistant high-entropy solid electrolyte according to claim 5, characterized in that: In step S1, the stirring and dispersing time is 90 to 240 minutes.
7. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane is made of the cold-resistant high-entropy solid electrolyte described in any one of claims 1 to 4.
8. The solid electrolyte membrane according to claim 7, characterized in that The thickness of the solid electrolyte membrane does not exceed 45 μm.
9. A lithium metal negative electrode, characterized in that The lithium metal negative electrode is obtained by compounding a lithium metal sheet and the cold-resistant high-entropy solid electrolyte according to any one of claims 1 to 4 using an in-situ method.
10. An all-solid-state lithium battery, characterized in that: It comprises a positive electrode, a lithium metal negative electrode and a solid electrolyte membrane located between the positive electrode and the lithium metal negative electrode, wherein the lithium metal negative electrode is the lithium metal negative electrode as claimed in claim 9, and the solid electrolyte membrane is the solid electrolyte membrane as claimed in claim 7 or 8.
Citation Information
Patent Citations
Electrolyte functional additive for lithium ion battery, lithium ion battery electrolyte and lithium ion battery
CN111509298A
Copolymerization solid electrolyte, preparation method thereof and solid polymer lithium battery
CN114024025A
Solid electrolyte, preparation method of solid electrolyte, lithium ion battery and preparation method of lithium ion battery
CN114300742A
Nonaqueous electrolyte solution, method for preparing same, secondary battery comprising same
CN117063321A
Composite polymer solid electrolyte and preparation method thereof, preparation method of high-entropy inorganic material and lithium ion battery
CN117133973A